FORMULASI BIOINSEKTISIDA NABATI BERBAHAN EKSTRAK BAWANG PUTIH (Allium sativum) DAN TEMBAKAU (Nicotiana tabacum) TERHADAP PENGENDALIAN HAMA DAN PERTUMBUHAN TANAMAN BAWANG MERAH (Allium ascalonicum) DAN BAWANG PREI (Allium fistulosum) DI KABUPATEN ENREKANG - Sunarti Sunarti; Zainal Potton; Cennawati Cennawati; Burnama Ashari; Suharman Suharman (STKIP Subang, 2026)
The continuous use of synthetic pesticides in the cultivation of shallot (Allium ascalonicum) and leek (Allium fistulosum) may cause adverse effects on the environment and human health, creating a need for more environmentally friendly pest-control alternatives such as bioinsecticides derived from natural materials. This study aimed to evaluate the effectiveness of bioinsecticide formulations made from garlic and tobacco extracts on pest attack intensity and pest mortality, as well as their effect on the vegetative growth and productivity of shallot and leek. The experiment employed a Completely Randomized Design (CRD) with seven treatments: a negative control (K0), a positive control (K+) using a synthetic pesticide with the active ingredient profenofos 500 g/L, and five bioinsecticide formulations (P1-P5), each replicated three times. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, one-way ANOVA, and post hoc tests (LSD or Games-Howell). The results showed that bioinsecticide treatments had a highly significant effect (P < 0.05) on all observed parameters. Treatment P2 (tobacco: garlic ratio = 2:3) was identified as the best bioinsecticide formulation, producing the lowest pest attack intensity among the bioinsecticide treatments and a corrected pest mortality (Abbott's formula) of 71.91% in shallot and 78.95% in leek. Application of P2 also had a positive effect on plant height, leaf number, tiller number, fresh weight, and dry weight in both commodities, with values numerically close to the positive control. Keywords: bioinsecticide, shallot, leek, pest mortality, plant growth